Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden - Örstan, Aydin (Zootaxa, 2018)
The morphological descriptions of the species of bdelloid rotifers and the associated taxonomic difficulties, primarily resulting from the inadequate original descriptions of many species, are discussed. The genus Adineta, whose members are relatively easy to study and frequently encountered, is proposed as a starting point for taxonomic revisions of the Bdelloidea. The taxonomically significant morphological traits in the genus Adineta are discussed. Some of these have rarely been used: the number of denticles on the rake organ and body proportions. These traits are used to describe Adineta beysunae sp. nov., which was found in a sample from a house garden. The new species is diagnosed by the morphology of its rump, foot and rake organ. The latter has up to 11 denticles, the highest number recorded in an Adineta species.